Character Education Through Al-Barzanji: A Study of Traditional Muslim Society in Tanjung Harapan Village, Seputih Banyak, Central Lampung - Athoillah, Athoillah; Siti Roudhatul Jannah; M. Sayyidul Abrori (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to examine the contribution of the Al-Barzanji reading tradition in shaping the character of traditional Muslim society in Tanjung Harapan Village, Seputih Banyak, Central Lampung. The problem raised in this study is how character values ​​such as deliberation, justice, compassion, and forgiveness are applied through the Al-Barzanji tradition and the challenges faced in integrating this tradition into people's lives. This study uses a qualitative method with a descriptive approach. The subjects of the study consisted of village heads, religious figures, people who are active in the Al-Barzanji tradition, and the younger generation in Tanjung Harapan Village. Data collection was carried out through observation, in-depth interviews, and documentation related to Al-Barzanji reading activities. Data validity testing was carried out through triangulation techniques by comparing the results of observations, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Al-Barzanji reading tradition still takes place in Tanjung Harapan Village and has an important role in instilling character values ​​in the community. The value of deliberation is reflected in the habit of deliberation before religious activities, the value of justice is seen in the attitude of mutual respect between citizens, compassion is manifested in harmonious social relations, and the attitude of forgiveness is practiced in everyday life. However, the challenges faced are the low interest of the younger generation in this tradition and the limited understanding of the community regarding the essence of character education in Al-Barzanji. Therefore, an innovative strategy is needed to maintain and develop this tradition as an effective medium for character education.